The role of coral reefs for marine life is as a place to find food, nursery areas, spawning grounds, and as hiding places: Pelestarian Transplantasi Terumbu Karang di Pulau Gag - Vicky Rizky Katili; Lay Tjarles; Muhamad Ali Ulat; Kadarusman Kadarusman; Amir M Suruwaky; Fataha Ilyas Hasan; Jusman Jusman; Lukman Efendi; Ismail Ismail (Buletin SWIMP, 2022)
The role of coral reefs for marine life is as a place to find food, nursery areas, spawning grounds, and as hiding places. Gag Island is one of the areas that has the potential for the main coral species Acropora sp, but with the increase in pollution from waste that causes sedimentation, and local community activities in fishing activities in ways that are not environmentally friendly, such as the use of bombs that make coral reefs in the area. many of these areas are degraded or damaged. To overcome the sustainability of fishing that is not environmentally friendly, it is the initiative to carry out socialization and transplantation.